A systematic review of psychosis in social work literature. Issue 5 (3rd September 2022) - Chaudhry, Serena; Roy, Robert; Weiss, Ashley; Hansel, Tonya
ABSTRACT: The RAISE trials highlighted the effectiveness of coordinated specialty care for psychosis. However, these publications are largely absent from the social work literature. We have reviewed nine major journals for papers related to psychotic disorders and their treatment since the RAISE trials. We found that five of the nine journals had no relevant articles, two had a single article, and the remaining journals had three and four articles, respectively. The RAISE trials were not mentioned in any of the papers. These results highlight the poor visibility of psychosis in social work. Poor visibility limits social work's ability to provide care despite its prevalence in adjacent fields.